At each step, if A(x,y) represents the number on (x,y), that number is increased by: \frac{(x-y) \left( A(x+1,y) + A(x,y-1) - A(x-1,y) - A(x,y+1) \right)}{4}
All the additions are done simultaneously.
1. Prove that the numbers at each point are always integers
2. Prove that, aside from the initial configuration, there is never a number that is divisible by 3
Solution
The recursion formula guarantees that A(x,y) is always a polynomial in x,y, with real coefficients. In the initial configuration, B(x,y) = A(x,y) + 1 = x^2+y^2 is homogeneous in x,y with degree 2. That is, B(kx,ky) = k^2 A(x,y). We will show that this homogeneity is maintained by the recursion formula, and therefore will hold true at all times.
Suppose A(x,y) = P.x^2 + Q.xy + R.y^2 - 1 for some real numbers P,Q,R then the recursion formula maintains it. This is because A(x+1,y) - A(x-1,y) cancels out the x^2,xy,y^2,1 terms, so only x,y terms are left. Similarly A(x,y+1) - A(x,y-1) will also only preserve x,y terms. So the second factor is homogenous with degree 1, but the factor (x-y) is also homogenous with degree 1, so the added number is homogeneous with degree 2. Therefore, the final number is still of the form A(x,y) = P'.x^2 + Q'.xy + R'.y^2 - 1 (for some P',Q',R' constants that may be different from the previous iteration).
Now we also notice that A(x,y) = A(y,x) for all time. This property is preserved in the beginning, but also preserved by the recursion, so the numbers are symmetric with respect to x,y. Therefore P = R.
Next, we notice that for x=y, the additions are always zeros, so A(x,x) = 2x^2-1 for all time. Therefore A(x,x) = (2P+Q)x^2-1 = 2x^2-1 so 2P+Q = 2.
This means that, because Q = 2- 2P, A(x,y) = Px^2 + (2-2P)xy + Py^2 - 1= (x^2+y^2 - 1) + (P-1)(x-y)^2 for some P real (not necessarily integer) that depends on t. So we've shown that A(x,y) has the form (x^2+y^2-1) + K_t(x-y)^2 for some K_t, where K_0 = 0.
Then, plugging in to the original recursion formula, we can see: (K_{t+1} - K_t)(x-y)^2 = \frac{x-y}{4} ( 4x - 4y +K_t(2(x-y+1)^2 -2(x-y-1)^2)) (K_{t+1} - K_t)(x-y)^2 = \frac{x-y}{4} ( 4x - 4y +8K_t(x-y)) K_{t+1} = 3K_t + 1 From there, it's a simple matter to see that K_t = \frac{3^t-1}{2} because K_0 = 0, but we didn't need to solve the recursion. The fact that K_0 = 0 is enough to prove that K_t is always an integer, and that, except for t=0, it's always \equiv 1 \mod 3.
Because K_t is always an integer then A(x,y) is also integral everywhere. And because K_t \equiv 1 \mod 3 then we can check that for any combinations of x,y \mod 3, A(x,y) will never be \equiv 0 \mod 3.
No comments:
Post a Comment